PEMIKIRAN PENDIDIKAN IBNU SINA - Alwizar Alwizar (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2015)
Ibnu Sina is an Islamic expert who master the various branches of knowledge. Specifically, Ibnu Sina is known in medical and philosophy field of his thought, and also his monumental report of medic, entitled “Al-Qur’an fi al-Tibb” which would be the reference of medical field for 5 century. Although known as an expert in philosophy and medic, but the several studies who conducted by the next generation about the thought of Ibnu Sina, found that several thoughts about the concept of Islamic education. In education, his thougts and ideas are exellent and able to be developed in the context of Modern Islamic Education which started by talking the nature of human because the educational subject is the human it self. Then, discussed also the educational objectives : to reach the happiness (sa’adah). Furthermore, the educational curriculum, the concept of Ibnu Sina’s curriculum formula is based on the level of age development of pupils. Finally, Ibnu Sina states that the educational method has to vary depend on the pupils pshicology development and the concept of teacher, educational significant for pupils and societes.